A framework of an ontology server for enhancing interlocking institutional worlds' integrity. (2015) - Ibrahim, Abdelrahman Abbas; Colomb, Robert M.; Ahmed, Abdelgaffar Hamid
Interlocking institutional worlds (IWs) are a collection of organisations interacting together in order to achieve some business goals. IWs need to interoperate semantically to exchange information. Ontologies are widely used to overcome the problem of interoperability and assist in simplifying interoperability between IWs' participants. Ontologies contain perdurant entities (entities that happen in time) as well as endurants (entities that exist in time). Ontology servers are information systems intended to manage ontologies. In this paper, we provide a specification of an ontology server to serve as a mechanism for binding IWs' information systems together in a specific domain and support them with agreed semantics to enhance their integrity.